Price theory - Ryan, William James Louden; Pearce, David W. (London : Macmillan, 1977)
The book is on game theory with the introduction of linearity into the chapters on consumer theory and on cost and production theory which is welfare economics.
Includes bibliographical references and index.
osa 03/01/2019
Loans
Keywords: Microeconomics